Dampak Pemanfaatan Platform Educaplay Terhadap Motivasi Belajar Siswa dalam Pembelajaran IPS di Kelas V Sekolah Dasar - Saija, Jackson Putra; Ode Abdurrachman; Nathalia Y. Johannes (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe student responses and engagement regarding the use of the Educaplay platform in Social Studies (IPS) lessons for fifth-grade students at SD Negeri 7 Ambon. A descriptive qualitative approach was employed, with the teacher and fifth-grade students serving as informants selected through purposive sampling. Data were collected via observation, interviews, and documentation, and subsequently analyzed descriptively. The results indicate that the use of Educaplay elicited positive student responses, reflected in three key aspects: attention and interest, active engagement and participation, and perseverance and focus during the lesson. Students demonstrated enthusiasm for learning activities, participated more actively, and responded positively to the use of digital media. These findings suggest that the use of Educaplay fosters student engagement in Social Studies lessons and positively influences learning motivation. Thus, Educaplay serves as a viable interactive digital learning medium to support more engaging, student-centered Social Studies instruction in primary schools.